PENGELOLAAN SAMPAH BERBASIS MASYARAKAT DALAM PENGUATAN KAPASITAS KELEMBAGAAN PEMBERDAYAAN KOMUNITAS PEREMPUAN DI DESA RIBANG KECAMATAN MUARA UYA KABUPATEN TABALONG - Raditia; Faridawati Erlina (Pojok Publisher, 2025)
Community-based waste management is an effective strategy for addressing environmental issues while strengthening the capacity of community empowerment. This study aims to examine the role of community women in waste management and its impact on increasing community awareness, participation, and independence in protecting the environment. The method used is a qualitative approach with data collection techniques through observation, interviews, and documentation in Ribang village, which has successfully implemented an independent waste management system. The results show that the active participation of community women in activities such as waste banks, household waste sorting, creating crafts from used waste, and composting have a positive impact on behavioral change and creating new economic value. In addition, support from government agencies through the Environmental Agency and CSR programs from PT. ADARO have also strengthened local institutional capacity and expanded the reach of empowerment. Waste management is not only a solution to environmental problems, but also a strategic tool in building a more caring, empowered, and independent community. Overall, this activity builds a strong institutional foundation and social capital for the sustainability of waste bank management at the village level, and opens up space for replication of similar models in other areas.